Pyrolysis of Natural Gas: Effects of Process Variables and Reactor Materials on the Product Gas Composition. Issue 3 (5th February 2019) - Wang, Steven; Lee, Woo Jin; Li, Chao'en; Kuan, Benny; Burke, Nick; Patel, Jim
Abstract: High‐temperature pyrolysis of natural gas is the basis of the standard method for the manufacture of acetylene. The study of methane pyrolysis was designed to find optimum process conditions that would produce high yields of acetylene with minimal carbon formation. High temperatures and short residence times enhanced the selectivity for acetylene, while hydrogen dilution was found to suppress the generation of carbonous products. Carbon formation on reactor surfaces over time may be mainly responsible for the misalignment of predicted and measured product gas compositions, as the mechanisms reported do not consider the surface chemistry. In essence, the pyrolysis system favors the highest possible temperature and shortest possible residence time, suggesting that the selection of reactor materials is the key for pyrolysis process optimization. The operating temperature is likely dictated by the physical properties of the reactor materials rather than the selection of optimal pyrolysis conditions. Abstract : Combining kinetic studies with computational fluid dynamics simulations, variables affecting C2 H2 selectivity and carbon deposition in pyrolysis of natural gas were studied, revealing that high temperatures and short residence times favor high selectivity for C2 H2 . H2 dilution suppresses overreaction of C2 H2 to produce carbon; low C2 H6 concentration has minimal effect on the pyrolysis of CH4 .